KNOWLEDGE MANAGEMENT AND ORGANIZATIONAL EFFECTIVENESS AS A SUCCESSFUL PATH TO GLOBALIZATION FOR SMALL AND MEDIUM ENTERPRISES - Vorobyova, Kateryna; Raju, Valliappan (PEOPLE: International Journal of Social Sciences, 2018)
The purpose of this paper is to study the influence of knowledge management as a critical component of organizational effectiveness, which in its turn influences a successful path to a globalization strategy for small and medium enterprises (SMEs). It is critical for SMEs that knowledge management be enable effectively and efficiently solving the problems, managing dynamic learning, strategic planning and decision making; by analyzing previous literature reviews on the subject of Knowledge management challenges of SMEs, regardless of the financial and human aspects. The significance of this study will affix the knowledge about current issues relating to SMEs in Malaysia in cognitive capital perspective. The article highlights the common issues related to knowledge management, which can be implemented successfully to a business strategy.